2019
DOI: 10.1007/s10681-019-2371-z
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular characterization of Ecuadorian quinoa (Chenopodium quinoa Willd.) diversity: implications for conservation and breeding

Abstract: Quinoa (Chenopodium quinoa Willd.) is recognized as an important crop to improve global food security. It has gained international recognition because of the nutritional value of its seeds and its broad agronomic resilience. Although several studies have attempted to characterize the genetic diversity of quinoa, none have focused on evaluating germplasm from Ecuador; the latter considered a relevant subcenter of diversity for the species. In this study, 84 accessions representing the species' cultivated range … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 27 publications
2
24
1
1
Order By: Relevance
“…During this study, the total number of bands (235) were found higher than reported by Hossein-Pour et al 2019using iPBS-retrotransposon markers, Ana-Cruz et al (2017) using ISSR markers, and Romero et al (2019) using SSR markers for quinoa germplasm. The average number of bands (21.4) found in this study were also higher than reported by recent studies (Salazar et al 2019;Romero et al 2019). Among the total 235 bands, 157 bands were found polymorphic and a number of polymorphic bands found in this study were higher than the reported by Romero et al (2019).…”
Section: Ipbs-retrotransposon As a Source Of Polymorphismcontrasting
confidence: 71%
“…During this study, the total number of bands (235) were found higher than reported by Hossein-Pour et al 2019using iPBS-retrotransposon markers, Ana-Cruz et al (2017) using ISSR markers, and Romero et al (2019) using SSR markers for quinoa germplasm. The average number of bands (21.4) found in this study were also higher than reported by recent studies (Salazar et al 2019;Romero et al 2019). Among the total 235 bands, 157 bands were found polymorphic and a number of polymorphic bands found in this study were higher than the reported by Romero et al (2019).…”
Section: Ipbs-retrotransposon As a Source Of Polymorphismcontrasting
confidence: 71%
“…This evidence came from the molecular and genetic diversity studies where just two Ecuadorian quinoa accessions were included [ 51 , 52 ]. Recently, a molecular characterization of diversity of Ecuadorian quinoa was conducted using 15 species-specific SSR markers on 84 quinoa accessions [ 53 ]. The results showed that Ecuadorian quinoa was highly diverse—196 alleles were detected, and the genetic heterozygosity ( H E ) was 0.71.…”
Section: Genetic Diversitymentioning
confidence: 99%
“…Seeds of 84 quinoa genotypes were collected from small farmers throughout the highlands of Ecuador (See also (Salazar et al 2019)). The material was propagated in The Netherlands, but viable seeds were obtained only from 40 genotypes.…”
Section: Plant Materialsmentioning
confidence: 99%
“…The low propagation success was attributed to low quality seed or late maturity of photoperiod-sensitive cultivars (Christiansen et al 2010). From the genotypes from which viable seed was obtained, 22 were selected that represent most of the genetic diversity as determined (Salazar et al 2019). Detailed information about these genotypes is presented in Table 1 and their collection-sites in the Ecuadorian highlands is shown in Figure 1.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation